(untitled) (Proceedings of International Educators Conference, 2024)
This thesis examines the alignment of Uzbekistan’s intellectual property (IP) legislation with the TRIPS Agreement, focusing on discrepancies and compliance levels between national laws and international standards. Through a detailed comparative analysis, the research identifies areas of divergence and proposes recommendations for improving Uzbekistan’s IP legal framework. The study highlights challenges faced by Uzbekistan in integrating global IP norms and provides actionable insights for enhancing legal and enforcement mechanisms.